2007
DOI: 10.1289/ehp.8869
|View full text |Cite
|
Sign up to set email alerts
|

Biomonitoring of 2,4-Dichlorophenoxyacetic Acid Exposure and Dose in Farm Families

Abstract: ObjectiveWe estimated 2,4-dichlorophenoxyacetic acid (2,4-D) exposure and systemic dose in farm family members following an application of 2,4-D on their farm.MethodsFarm families were recruited from licensed applicators in Minnesota and South Carolina. Eligible family members collected all urine during five 24-hr intervals, 1 day before through 3 days after an application of 2,4-D. Exposure profiles were characterized with 24-hr urine 2,4-D concentrations, which then were related to potential predictors of ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
1
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(57 citation statements)
references
References 24 publications
1
53
1
2
Order By: Relevance
“…Apart from a dose-dependent decrease in body and kidney weights, changes in the kidney morphology at light microscopical level (Table 2) was observed distinctly in this dose range, indicating the congruity of the dose range selected. Morover, a recent study has evaluated 2,4-D exposure in farm family members in Minnesota and South Carolina of United States on their farm and the geometric mean systemic doses were found 2.46, 0.8 and 0.22 lg/kg in applicators, spouses and children, respectively (Alexander et al 2007). This study has revealed a considerable heterogeneity of 2,4-D exposure among farm family members and showed that exposure to the spouses and children is primarily determined by direct contact with the application process and the number of acres treated.…”
Section: Resultsmentioning
confidence: 99%
“…Apart from a dose-dependent decrease in body and kidney weights, changes in the kidney morphology at light microscopical level (Table 2) was observed distinctly in this dose range, indicating the congruity of the dose range selected. Morover, a recent study has evaluated 2,4-D exposure in farm family members in Minnesota and South Carolina of United States on their farm and the geometric mean systemic doses were found 2.46, 0.8 and 0.22 lg/kg in applicators, spouses and children, respectively (Alexander et al 2007). This study has revealed a considerable heterogeneity of 2,4-D exposure among farm family members and showed that exposure to the spouses and children is primarily determined by direct contact with the application process and the number of acres treated.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, a lack of biological plausibility is further affirmed by the extremely large margin of exposure between biomonitored 2,4-D doses reported for male farm-worker applicators in the Ag Health Study itself and the NOEL dose for thyroid effects in rats reported by Stoker. The Alexander et al (2007) study of farm families identified a geometric mean exposure dose for male applicators of 2.46 lg/kg/day, which is approximately 10 000X below the NOEL of 30 mg/kg/ day (30 000 lg/kg/day) for thyroid effects identified by Stoker and Zorrilla (2010). Importantly, the geometric mean dose for female spouses living in close proximity to active 2,4-D application operations was 0.08 lg/kg/day, and was substantially disparate (> 300 000) from the approximately 25 mg/kg/day dietary dose identified as the inflection point for onset of TSRC in female rats (a non-thyroid toxic dose in rats).…”
Section: Woe Evaluation For Potential Effects Of 24-d On the Hpt Axismentioning
confidence: 83%
“…This NOAEL is based on renal toxicity, not on endocrine or reproductive effects. Alexander et al (2007) reported that children living on farms on which 2,4-D was being actively applied had systemic doses (geometric mean) of 0.32 (children 4-11) to 0.12 (children >12 years old) lg/kg based on five days of comprehensive urinary biomonitoring. These dose levels were 65 625-175 000-fold below the overall NOAEL of 21 mg/kg/day (21 000 lg/kg/ day) used to set the EPA chronic reference dose for 2,4-D. Large margins of exposure (MOEs) were similarly noted for both applicators and spouses (geometric mean systemic doses of 2.46 and 0.8 lg/kg/day, respectively).…”
Section: Differentiating Potential Endocrine Modes Of Action Based Onmentioning
confidence: 99%
See 1 more Smart Citation
“…Children of agricultural workers may have a higher risk of exposure to pesticides compared to the general populations because of the close proximity of their homes to the fields where pesticides are applied and from take-home exposure (Fenske, et al, 2002;Loewenherz, et al, 1997). Although pesticide metabolite levels were not significantly increased in spouses and children living on a farm during pesticide applications, children who had contact or were observing the mixing or application had higher metabolite levels than those who were out of the area when pesticides were mixed or applied (Acquavella, et al, 2005;Alexander, et al, 2007). While information is available on the impact of acute exposure in adults and occupational exposure, little information is available examining the impact of exposures in children.…”
Section: Assessment Of Neurobehavioral Effects In Vulnerable Populatimentioning
confidence: 99%